PRAKTEK PENGUNGKAPAN SOSIAL PADA LAPORAN TAHUNAN DI PERUSAHAAN-PERUSAHAAN YANG TERDAFTAR DI PT BURSA EFEK INDONESIA PADA TAHUN 2016 - Era Delena (Media Riset Akuntansi, Auditing & Informasi, 2017)
This paper is mainly to get the new perspective on those Indonesian go public companies, which listed in Indonesia Stock Exchange, that presently practice the social disclosure on their annual report and at the same time also aims to find out the type of the industries, size of the companies and the ownership of the companies which effect on the practice of social disclosure in those companies that listed in Indonesia Stock Exchange. Social disclosure practice is divided into 6 categories, among others : environment, energy, employee, product/consumer, society and share holders. Industrial type is divided into: sensitive and non-sensitive industrial. Company ownership is divided into two types: domestic ownership and foreign ownership. While the size of the company is measured based on the  total  asset belongs to the company. These researched data is obtained from 45 public listed companies in Indonesia Stock Exchange by using simple random sampling with multiply regression data analysis method.Based on the regression test with Anova Table, it is known that F 7.362 with p-value 0,000 < alpha 0,05 hence Ho is refused, which means the type, size and ownership of the companies altogether will effect the social disclosure on the annual report on those listed companies at Indonesia Stock Exchange in 2016.